The Influence of Environmental Factors on Firm Financial Performance - Luthan, Elvira; Zen, Sri Daryanti; Dwinanda, Vioni Putri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This article aims to empirically discuss the effect of environmental performance, environmental costs, and environmental disclosure on the Firm's financial performance. This study measures the Firm's financial performance by return on assets (ROA). We selected the research population as all manufacturing sector companies on the Indonesia Stock Exchange. The sample of this study was all manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sampling technique used in this study was purposive sampling, and 16 manufacturing sector companies met the requirements for research samples. This study used the SPSS version 29 application software as an analysis tool. The results of this study indicate that environmental performance does not affect financial performance. Environmental costs affect economic performance. Environmental disclosure does not affect financial performance. These results contribute to academics and practitioners because it turns out that corporate sacrifices in caring for the environment positively impact the Company.